Rancang Bangun Alat Kontrol Lampu Jarak Jauh Menggunakan Mikrokontroler Berbasis Website - Laban Yoel Ishak Frare; Samuel Ramos (Sistem Komputer & Teknologi Intelegensi Artifisial (SIKOMTIA), 2022)
It is very important to pay attention to the management of electrical devices in spaces for human activity related to the specified time when the time is on and when it is off to avoid wasting energy using wasted energy. There are several procedures for managing electricity that has been implemented using renewable technology in the current era of industrial trends 4.0, including controlling lights and other electrical devices. In general, light control uses manual procedures by turning on the switch directly, starting from offices, shopping centers, public places and others. In this modern era, it is possible for humans to use technological updates by changing the use of light switches to become automatic using a microcontroller control board and a wifi module as a transmission medium that is integrated with the web as a portal for monitoring light points installed in a building or facilities. general. This study aims to obtain new habits of the community regarding the use of automatic light control devices in order to save on the cost of using electricity. This change is also beneficial for everyone who is outside the house in their daily life, so they don't have to go home when they want to turn on the lights. By using the website platform, electrical devices located in different rooms can be controlled via cell phones and can also be controlled via computers or gadgets.